2012
DOI: 10.1016/j.jjcc.2011.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pulse wave velocity in systemic lupus erythematosus, rheumatoid arthritis and Behçet's disease

Abstract: Pulse wave velocity was found to be high in chronic inflammatory connective tissue diseases compared to the control group. However, no difference was found between groups. Age was determined as the most important independent variable in the regression analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 32 publications
3
13
1
1
Order By: Relevance
“…Cf-PWV was significantly correlated with age, hsCRP, HOMA-IR and apo A-I levels. Age, hsCRP and DAS-28 have been previously identified as independent predictors of arterial stiffness in RA patients [17,31]. However, in the present study, a crucial role was also pointed out for plasma levels of apo A-I.…”
Section: Discussioncontrasting
confidence: 48%
“…Cf-PWV was significantly correlated with age, hsCRP, HOMA-IR and apo A-I levels. Age, hsCRP and DAS-28 have been previously identified as independent predictors of arterial stiffness in RA patients [17,31]. However, in the present study, a crucial role was also pointed out for plasma levels of apo A-I.…”
Section: Discussioncontrasting
confidence: 48%
“…In patients with systemic lupus erythematosus examined in the present study the average PWV was 8.87 ±2.1 m/s and it was significantly higher as compared to the control group matched for gender and age. The results are similar to those reported by Yildiz et al [21] (8.98 ±2.05 m / s). Other authors found even higher values of PWV.…”
Section: Resultssupporting
confidence: 92%
“…Other studies have reported that aortic PWV was correlated with elevated CRP, ESR, and DAS-28 [14]. Age and DAS-28 have also been previously determined as independent predictors of AS in RA patients [25,9]. Lee et al evaluated local CS in RA patients by speckle tracking strain imaging and found that local CS had a significant correlation with age, disease duration, and DAS-28 [23].…”
Section: Discussionmentioning
confidence: 99%